2019
DOI: 10.1108/jkm-07-2018-0433
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management competences, exporting and productivity: uncovering African paradoxes

Abstract: Purpose This study aims to investigate the importance of relational and conditional knowledge by assessing how service and signaling competences affect manufacturing firms’ productivity. These relationships are explored in the context of Africa, where, paradoxically, firms selling abroad must satisfy different market demands than firms that serve only domestic markets. Design/methodology/approach The authors draw on the World Bank Enterprise Survey to perform a cross-sectional analysis of 4,683 manufacturing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 117 publications
(225 reference statements)
2
38
0
Order By: Relevance
“…Although the results obtained cannot be generalized due to the methodological limitations of case studies, these results highlight the importance of geographical interconnectivity for territorial and organizational competitiveness (Growe, 2019;Lafuente et al, 2017;Vendrell-Herrero and Wilson, 2017;Vendrell-Herrero et al, 2019).This article shows the importance of geographical proximity in establishing strategic relationships aimed at strengthening service deployment in manufacturing companies (Bustinza et al, 2019a;Vendrell-Herrero and Wilson, 2017).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Although the results obtained cannot be generalized due to the methodological limitations of case studies, these results highlight the importance of geographical interconnectivity for territorial and organizational competitiveness (Growe, 2019;Lafuente et al, 2017;Vendrell-Herrero and Wilson, 2017;Vendrell-Herrero et al, 2019).This article shows the importance of geographical proximity in establishing strategic relationships aimed at strengthening service deployment in manufacturing companies (Bustinza et al, 2019a;Vendrell-Herrero and Wilson, 2017).…”
Section: Discussionmentioning
confidence: 82%
“…At the same time, this result suggests a new emerging relationship, as it shows a positive connection between the servitization capacity, the perceived impact of the KIBS company, and partner's (i.e., KIBS firm's) proximity. Based on these results, it can be concluded that there was a positive relationship that 0 1 2 3 4 demonstrates the importance of geographical proximity for firms pursuing collaboration strategies with a KIBS partner aimed at integrating complementary services as a new competitive source of value (Lafuente et al, 2017;Growe, 2019;Vendrell-Herrero et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…More generally, we believe that innovation varies both in the continuous space and in different territories (Doloreux & Shearmur, 2012). In any case, traditional theories that apply to Western economies may not apply to less developed countries (Hsieh et al, 2015;Vendrell-Herrero et al, 2019). The present research examines these relationships in the developing economies of Latin America; the finding of somewhat similar results to those of advanced economies being an important contribution.…”
Section: Introductionmentioning
confidence: 74%
“…The dependent variable, KIBS co-location, is the share of firms in technological services (T-KIBS) as the total service firms in a city where a manufacturing firm is located and is measured at the countrycity level using the method first described in Vendrell-Herrero et al (2019). In deriving our measurement of KIBS, we differentiate between service firms in the IT sector and service firms in other service industries, including the retail sector.…”
Section: Description Of Variablesmentioning
confidence: 99%